Endoplasmic reticulum stress activates the hepatic activator protein 1 complex via mitogen activated protein kinase-dependent signaling pathways. - Shantel Olivares; Richard M Green; Anne S Henkel (PLoS ONE)
Background and aims Endoplasmic reticulum (ER) stress is induced in many forms of chronic liver disease and may promote the development of hepatocellular carcinoma. The activator protein 1 (AP-1) complex is a transcription factor that promotes hepatic carcinogenesis in response to cellular stress. The aim of this study was to determine the role of ER stress in the regulation of the hepatic AP-1 complex. Methods Human hepatocellular carcinoma (HepG2) cells and C57BL/6J mice were subjected to pharmacologic ER stress and the expression of AP-1-associated genes and proteins was assessed. To determine the role of MAPK signaling in ER stress-induced AP-1 activation, ER stress was induced in JNK- and ERK-inhibited HepG2 cells. Results Induction of ER stress promoted the activation of both Jun- and Fos-related genes and proteins of the AP-1 complex in HepG2 cells and murine liver. Inhibition of ERK phosphorylation in HepG2 cells completely prevented ER stress-induced activation of the fos-related components of AP-1 whereas activation of Jun-related components was only partially attenuated. Conversely, inhibition of JNK phosphorylation in HepG2 cells reduced ER stress-induced activation of Jun-related components but did not prevent activation of fos-related components. Conclusions ER stress activates the hepatic AP-1 complex via MAPK-dependent signaling pathways. ER stress-induced activation of Fos-related components is dependent primarily on ERK activation whereas ER stress-induced activation of Jun-related components is dependent primarily on JNK activation, although there is interplay between these regulatory pathways. These data implicate a novel signaling pathway by which sustained ER stress, as observed in many chronic liver diseases, may promote hepatic carcinogenesis.